Konsentrasi Eco Enzyme berbasis Sumber Daya Lokal Ternate Mendukung Pertumbuhan Tanaman Kailan (Brassica oleracea var. achepala) - Moh Zulizar; Suratman Sudjud; Zauzah Abdullatif (Jurnal Pertanian Khairun, 2022)
This study aims to examine the concentration of Eco-enzymes based on local Ternate resources in dealing with the greed of Tutman Kailan which was carried out in the Tabam sub-district, North Ternate district. The study used a factorial completely randomized completely randomized design (CRD) with two factors as the main factors. Concentration of top taluk ecoenzyme Eight concentrations of top taluk taluk without concentration (R0) to 7 ml/l water (R7) and lead factor. Kailan seed variety that talukat consists of two varieties, namely the Daily Fram variety and the red arrow variety. The tools used in this study were digital scales, ruler, caliper, spoon, 5 kg polybag, digital camera, sack, label, stationery, paper, hoe. The materials used in the research were soil media, kailan seed, Eco-enzyme. The research was carried out in several stages, namely the manufacture of eco enzymes, preparation of planting media, planting, and data collection. The results showed that the concentration of eco-enzyme based on local resources in Ternate did not have an interaction effect but gave a singular effect, a concentration of 5 ml/l water (R5) resulted in the highest plant height of 34 cm and the number of leaves 7.67 while in leaf area, 2006, 85 cm at a concentration of (R7) 7ml/water but not different from R5. Variable stem diameter Plant fresh weight and root dry weight had no significant effect, while the total fresh weight of treatment R5 gave the highest fresh weight of 280 g in the red arrow variety (V2) as well as the total dry weight of 23.37 g in treatment R5 but the difference variety has no effect.Keywords: Concentration of eco enzyme, local resources, kailan plant